2018
DOI: 10.11118/actaun201866040939
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phytogenic Additive on Behavior During Mild-Moderate Heat Stress in Broilers

Abstract: The aim of this study was to evaluate the effect of phytogenic additive with anti‑inflammatory and antioxidant properties on thermoregulatory behavior (lifting of the wings, high respiratory rate defined as open beaks) and water and feed intake in mild‑moderate heat stressed Cobb 500 broiler chickens. From 28th day of chickens’ age experimental group was supplemented with 0.1 % phytogenic additive based on Scutellaria baicalensis L. extract in the diet. At the age 30 days temperature was increased to 27 °C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Consequently, OP could decrease endogenous heat production, resulting in less panting behaviour. Similar to our results, reduced panting behaviour has also been reported by others when broiler or quail diets were supplemented with polyphenols [62,88] or other antioxidants such as propolis [87], a combination of ascorbic acid and betaine [89] and phytogenic additives [90]. The promising results observed in this study with regard to the positive nutritional effect of OP on the thermal comfort and welfare of broilers are of great importance for the poultry sector.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, OP could decrease endogenous heat production, resulting in less panting behaviour. Similar to our results, reduced panting behaviour has also been reported by others when broiler or quail diets were supplemented with polyphenols [62,88] or other antioxidants such as propolis [87], a combination of ascorbic acid and betaine [89] and phytogenic additives [90]. The promising results observed in this study with regard to the positive nutritional effect of OP on the thermal comfort and welfare of broilers are of great importance for the poultry sector.…”
Section: Discussionsupporting
confidence: 91%
“…Both baicalin and curcumin are viewed as potent anti-stress agents, capable of modulating the HPA axis ( 56 , 57 ). Offering curcumin has been recently shown to reduce laying hen corticosterone levels in heat stress conditions ( 14 ), while SCUT extract has been shown to modify the thermoregulatory behavior of broilers raised in moderate HS conditions ( 58 ). Corticosterone has pro-oxidative functions leading to increased mitochondrial metabolism ( 59 ), increases energy deposition at the expense of reproductive function ( 60 ), and may lead to decreased steroidogenesis and as a result impaired ovarian development and function ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, this stress can increase aggressive and negative social behavior such as fighting, feeder occupying, tail biting [18,19] and the incidence of body lesions [20][21][22]. Supplementaion of Scutellaria baicalensis L. roots mitigated negative behavior caused by heat stress in mono-gastric animals [23,24]. However, studies on the relationship between high stocking density and PFA have not been reported.…”
Section: Introductionmentioning
confidence: 99%